The Effect Of Lavender Aromatherapy On Dysmenore In Adolescent Females At SMA PAB 5 Klumpang - Indah Dewi Sari; Utari Dwi Listiarini; Mayang Wulan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The incidence of dysmenorrhea is quite high in the world. The average incidence rate is 1,769,425 people (90%) who experience dysmenorrhea. The prevalence of dysmenorrhea in Indonesia is quite high, namely 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. It is estimated that as many as 90% of women in Indonesia have experienced dysmenorrhea but do not report it to health services. Severe dysmenorrhea can interfere with daily activities, forcing sufferers to rest and leave school activities. Pain management can be done by adolescent girls if they are told how to handle it non-pharmacologically using non-pharmacological methods, one of which is by administering lavender aromatherapy. The purpose of this study was to determine the effect of Lavender Aromatherapy on reducing pain scales in adolescent girls at PAB 5 Klumpanga High School. This study is useful for increasing knowledge and information about how to reduce menstrual pain scales by administering lavender aromatherapy. This study is a type of pre-experimental research with the design used is a pre-test post-test one group using lavender aromatherapy intervention. The population in this study were all high school female adolescents in grade X as many as 15 people. Sampling used a purposive sampling technique, namely 15 people. The data collection instrument used the NRS observation sheet, then the data were analyzed using univariate and bivariate analysis. Bivariate analysis used a paired sample t-test comparison test with a significance level of 0.05). The study showed a decrease in pain intensity pre-test and post-test, namely in the post-test the majority experienced moderate pain as many as 9 respondents (60%) and severe as many as 6 respondents (40%). After the intervention, the majority experienced mild pain as many as 8 respondents (53.3%) and a minority experienced moderate pain as many as 7 respondents (46.7%). The results of the paired t-test obtained p-value = 0.000 (<0.05) which means there is a difference in the average pre-test and post-test. There is an effect of giving lavender aromatherapy on dysmenorrhea at SMA PAB 5 Klumpang in 2025. It is hoped that schools will provide lavender aromatherapy in schools to reduce dysmenorrhea.